Analysing blockchain adoption in beekeeping: application of theoretical models and their effectiveness - Ornelas Herrera, Selene Ivette; Baba, Yasmina; Erraach, Yamna; Ouertani, Emna; Arfa, Lamia; Çamoğlu, Seval Mutlu; de-Magistris, Tiziana; Kallas, Zein (Frontiers in Sustainable Food Systems, 2025)
In 2022, the EU coordinated action “From the Hives” (Honey 2021–2022) revealed that 46% of imported honey in the EU did not comply with the “Honey Directive” and is suspected of adulteration. Nowadays the blockchain ecosystem is a digital technology that could be used to trace honey, assisting in fraud reduction and ensuring the authenticity of the botanical and geographical origin of the honey. Nevertheless, its implementation is limited by stakeholders’ acceptance, particularly beekeepers’ decisions. With the aim of identify principal factor affecting beekeepers blockchain adoption, this study applied two theoretical models at the farm level, related to technology adoption: The Theory of Planned Behavior (TPB) and the Technology Adoption Model (TAM). In both models, an additional construct identified as digital maturity was included, analysing their impact on the intention to adopt blockchain through the PLS-SEM method. General findings show that all constructs of both extended models influence the intention to adopt blockchain. Especially, the extended TAM model showed better results than extended TPB according to the explained variance (64.0 and 62.0% respectively). In these models, the perceived behavioral control of TPB and the usefulness perception of TAM were the major predictors of intention to adopt blockchain. Moreover, the digital maturity of farmers was a pivotal factor in enhancing the adoption of such innovations. The findings indicated that implementing blockchain necessitates the provision of training and resources to enhance beekeepers’ competencies, thereby augmenting their trust and proficiency in utilizing digital technologies. Furthermore, the creation of user-friendly interfaces is critical for acceptance, emphasizing the importance of a collaborative process between blockchain designers and beekeepers.